2020
DOI: 10.2147/dddt.s213968
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cost-Effectiveness Analysis of Ezetimibe as the Add-on Treatment to Moderate-Dose Rosuvastatin versus High-Dose Rosuvastatin in the Secondary Prevention of Cardiovascular Diseases in China: A Markov Model Analysis</p>

Abstract: Background: For patients with inadequate control of cholesterol using moderate-dose statins in the secondary prevention of cardiovascular diseases (CVD), either doubling the dose of statins or adding ezetimibe should be considered. The cost-effectiveness of them is unknown in the Chinese context. The aim of this study is to compare the cost and effectiveness of the two regimens, and estimate the incremental cost-effectiveness ratio (ICER).Methods: A Markov model of five health statuses were used to estimate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…Authors from studies not reporting cost year were contacted by e-mail in an effort to complete the missing data. In addition, results from Permpanich et al [31] and Yang et al [32] could not be adapted due to the lack of data on purchasing power parities. Korman and Wisloff [33] reported cost results in Euros but the study was based in Norway, and Lin et al [34] reported costs in international dollars but the study was set in five low-and medium-income countries (LMIC), and both studies were excluded from cost adjustment.…”
Section: Cost Adjustments Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors from studies not reporting cost year were contacted by e-mail in an effort to complete the missing data. In addition, results from Permpanich et al [31] and Yang et al [32] could not be adapted due to the lack of data on purchasing power parities. Korman and Wisloff [33] reported cost results in Euros but the study was based in Norway, and Lin et al [34] reported costs in international dollars but the study was set in five low-and medium-income countries (LMIC), and both studies were excluded from cost adjustment.…”
Section: Cost Adjustments Methodsmentioning
confidence: 99%
“…The general characteristics of the included articles organised by treatment strategies are summarised in Table 1. Of the selected studies, ten evaluated ezetimibe [12,13,32,33,35,36,[42][43][44][45], 15 PCSK9 inhibitors [12, 26, 28-30, 33, 37-39, 43-48], five n-3 PUFAs [31,40,[49][50][51], and seven the polypill [27,34,41,[52][53][54][55]. Four out of the 15 studies focusing on PCSK9 inhibitors also reported the ICERs of ezetimibe versus statins, but considering ezetimibe as a comparator [12,33,43,44], and those results have also been included and reported in this review.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] In countries with low per capita gross domestic product, a 97% reduction would be considered costeffective. [20] The results of some studies are cost-effective when ezetimibe is added to ongoing statin therapy and the costs and bene ts of maintaining current doses of statin therapy [21]. However, in a 5-10 year follow-up model, ezetimibe combined with statin therapy is not a cost-effective alternative, but when the follow-up period is extended to a lifetime, combination therapy becomes a cost-effective treatment.…”
Section: Discussionmentioning
confidence: 99%